Application of Random Mutagenesis and Synthetic FadR Promoter for de novo Production of ω-Hydroxy Fatty Acid in Yarrowia lipolytica - Park, Beom Gi; Kim, Junyeob; Kim, Eun-Jung; Kim, Yechan; Kim, Joonwon; Kim, Jin Young; Kim, Byung-Gee (Frontiers in Bioengineering and Biotechnology, 2021)
As a means to develop oleaginous biorefinery, Yarrowia lipolytica was utilized to produce ω-hydroxy palmitic acid from glucose using evolutionary metabolic engineering and synthetic FadR promoters for cytochrome P450 (CYP) expression. First, a Y. lipolytica base strain was constructed to produce free fatty acids (FFAs) from glucose using metabolic engineering strategies. Subsequently, through EMS induced random mutagenesis and FACS screening, improved FFA overproducers were screened. Additionally, synthetic promoters containing bacterial FadR binding sequences for CYP expression were designed to respond to the surge of the concentration of FFAs to activate ω-hydroxylating pathway, resulting increased transcriptional activity by 14 times from the third day of culture compared to the first day. Then, endogenous alk5 was screened and expressed using the synthetic FadR promoter in the developed strain for the production of ω-hydroxy palmitic acid. By implementing the synthetic FadR promoter, cell growth and production phases could be efficiently decoupled. Finally, in batch fermentation, we demonstrated de novo production of 160 mg/L of ω-hydroxy palmitic acid using FmeN3-TR1-alk5 in nitrogen limited media. This study presents a good example of the production of ω-hydroxy fatty acids using synthetic promoter with bacterial transcriptional regulator (i.e. FadR) binding sequences in oleaginous yeasts.